Accountable to who, to whom, for what and how? Unpacking Accountability in Local Government Response to Climate Change - Brett Quayle; Nick Sciulli; Elisabeth Wilson-Evered (Australasian Accounting, Business and Finance Journal, 2020)
The aim of this exploratory study is to delineate the role of local government in climate change response through an accountability lens. Local governments have an important role in climate change response due to its proximity to the impact the environment will have on its citizens and businesses. Understanding the roles and responsibilities of local government response to climate change, therefore, needs a critical exploration of the ways in which local governments are answerable on its obligations. Local government climate change response was investigated by posing questions aimed to unpack accountability: who, to whom, for what, and how? Findings from the investigation show that climate change response within local councils is a highly contextual phenomenon; where the level of accountability observed is influenced externally by community demands and political cycles, and internally through a hierarchical chain of command, collaboration amongst council workers and the political interests of its leaders. The current study contributes to the literature by deepening understanding of how individuals make sense of organisational initiatives that respond to climate change, as well as highlighting the accountability challenges faced within local governments.
Keywords: M40; Q56